A historical companion to postcolonial literatures in English - Poddar, Prem; Johnson, David, 1962 May 20- (Edinburgh University Press, 2008)
"From the triumphs of nationalism and political and cultural independence to the continuing problems of internal strife and poverty, postcolonial nations have grappled with a range of political, intellectual, and economic issues. A Historical Companion to Postcolonial Literatures in English is a comprehensive introduction to the major events, figures, and movements that have shaped the postcolonial history of the Anglophone world. With entries from more than fifty leading scholars arranged alphabetically by topic, this volume brings together the postcolonial histories of Africa, the Middle East, South Asia, Southeast Asia, Australia, New Zealand, the Pacific, the Caribbean, and Canada. Each entry provides a summary of a historical event or topic and suggestions for further readings. The volume also includes substantive essays on historiography and women's histories. By outlining the cultural, social, and political contexts of postcolonialism as well as examining elements of colonial history, this companion illuminates complex contemporary debates about globalization, AIDS, immigration, race, politics, economics, culture, and language."--Publisher